Prospective Study on the Incidence of Hospital Acquired Infections in Intensive Care Unit: Incidence of Hospital Acquired Infections - Hayee Phulpoto, Abdul; Aziz, Asif; Memon, Abdul Qayoom; Channa, Munir Ahmed; Pervez, Safdar Ali; Ramani, Ratan Kumar (Pakistan Journal of Health Sciences, 2025)
Hospital-Acquired Infections (HAIs) in the ICU significantly impact patient morbidity, mortality, and length of stay. Objective: To determine the incidence of HAIs, identify key risk factors, and analyze their impact on clinical outcomes in ICU patients. It was prospective observational study. Methods: A total of 220 ICU patients were included. Data on demographics, ICU stay duration, device use (e.g., central lines, ventilators, urinary catheters), comorbidities, and infection control practices were collected. HAIs were diagnosed based on CDC definitions and categorized as Ventilator-Associated Pneumonia (VAP), Central Line-Associated Bloodstream Infection (CLABSI), Catheter-Associated Urinary Tract Infection (CAUTI), and Surgical Site Infections (SSI). Incidence rates were calculated using descriptive statistics, and risk factors were identified through multivariate logistic regression. Results: Results showed that 150 (68.2%) patients developed HAIs, with VAP being the most common (30%), followed by CAUTI (16.7%), CLABSI (20%), and SSI (13.3%). Independent risk factors for HAIs included ventilator use (p<0.001), prolonged ICU stay (p=0.004), and use of urinary catheters (p=0.002) and central lines (p=0.003). Patients with HAIs had higher mortality (30% vs 12%, p=0.003) and longer ICU stays (21 days’ versus 12 days, p<0.001). Conclusions: HAIs are frequent in ICU patients, particularly VAP. They significantly increase mortality and prolong ICU stays, highlighting the need for enhanced infection control practices, especially for patients with extended ICU stays or those requiring invasive devices.